ISOLASI DAN KARAKTERISITK JAMUR PELAPUK DARI BATANG DAN TANDAN KOSONG KELAPA SAWIT - Muh. Yusuf Idris; Sukriming Sapareng; Irwan Halid (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
Rot fungus has the ability to degrade stem and empty fruit bunches oil palm for producing an enzyme that can break down cellulose, hemicellulose, and lignin. Fungal isolates obtained from stem oil palm  which had rotted and empty fruit bunches oil palm. Isolates were observed macroscopically and microscopically. Macroscopic observation includes growth speed, colony color, elevation and the edge of the colony. Microscopic observations include the shape of fungal spores and conidiophores. The research found rot fungi are 32 isolates comprising 17 isolates from oil palm stem decaying and 15 isolates from empty fruit bunches oil palm. Trichoderma isolates sp3 colony having a diameter of highs, lows and Absidia sp isolates were grown on PDA.